Detailed investigation on how the protein corona modulates the physicochemical properties and gene delivery of polyethylenimine (PEI) polyplexes. (21st May 2018) - Zhu, Dingcheng; Yan, Huijie; Zhou, Zhuxian; Tang, Jianbin; Liu, Xiangrui; Hartmann, Raimo; Parak, Wolfgang J.; Feliu, Neus; Shen, Youqing
Abstract : Given the various cationic polymers developed as non-viral gene delivery vectors, polyethylenimine (PEI) has been/is frequently used in in vitro transfection. Abstract : Given the various cationic polymers developed as non-viral gene delivery vectors, polyethylenimine (PEI) has been/is frequently used in in vitro transfection. However, the primary drawback limiting its in vivo applications is the sharp decrease in transfection efficiency in the presence of serum. Here, we investigated the influences of serum proteins or bovine serum albumin (BSA) on the physicochemical properties of PEI/DNA complexes (polyplexes), including hydrodynamic diameters and agglomeration behavior, zeta potentials, morphologies, and sensitivity to the presence of salt. Mechanism studies revealed that the protein corona determined the endocytic rates and pathways, intracellular transport, the rate of endo/lysosomal trafficking, vesicle escape efficiency, and thus the overall gene expression levels. This work offers mechanistic insights for the serum-induced suppression of transfection efficiency, which is the reduced endo/lysosomal escape of the protein-coated polyplexes, in contrast to the protein free polyplexes.